Pengembangan Teknologi Tepat Guna Erp Untuk Modul Crm (Kampoeng Kuliner Brenzeel 48) - Agus Darmawan; Dwi Tjahjo Seabtian (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
Development of the application of Enterprise Resource Planning (ERP) as one of the supports for the operation of a business field that is integrated with business and has better data accuracy. An ERP system consists of various modules and sub-modules that can represent specific business components. If data is entered in a module (eg data on rice uduk sales) then other modules such as payment and inventory will be automatically updated as well. These updates occur in real time or right at the time of the sale. Implementation of Customer Relationship Management (CRM) or customer relationship management which is indirectly said to be computerized customer data. This is so that the company knows what the needs and desires of customers are so that good relationships can be established with customers. Many companies focus on high satisfaction because many dissatisfied customers are easy to think about getting a better offer. Those who are very satisfied have a harder time changing their minds. High satisfaction or pleasure creates emotional attachment to the company